Edukacja religijna a epoka ponowoczesna - Jarosław Michalski (Nicolaus Copernicus University in Toruń, 2009)
Religious education in epoch of postmodernity  The author of the article presents the variants of new understanding of religious education in epoch of postmodernity. He tries to do it from historical and contemporary perspective, indicating false and unjustified alternative thinking about religion and education as a person's development. In the article religious education is defined as education going out from a person and orientated towards a person, that means that a person as an individual is a central moment of educational process. In author's opinion, religious education understood in such a way gives an opportunity for a person's integral development. The article proves that religious education realizes individual person's development joint with positive conception of person's freedom and with specific idea of good in the most complete way. No doubt these are factors not only conditioning the possibility of defining person's own identity but also enabling to overcome postmodern ambivalence of reality that surrounds contemporary person.